Matematyka

Autorzy:Karolina Wej, Wojciech Babiański, Ewa Szmytkiewicz, Jerzy Janowicz

Wydawnictwo:Nowa Era

Rok wydania:2016

Zapisz wyrażenie w prostszej postaci, a następnie 4.25 gwiazdek na podstawie 8 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

`a) \ \ (x^7*x^(-3))/x^(-2)=x^(7-3)/x^(-2)=x^4/x^(-2)=x^(4-(-2))=x^(4+2)=x^6` 

`(-2)^6=64`

`b) \ \ (x^6*x^(-3))/(x^4*x^(-5))=(x^(6-3))/(x^(4-5))=x^3/x^(-1)=x^(3-(-1))=x^(3+1)=x^4` 

`3^4=81` 

`c) \ \ (8*x^(-6)*x^5)/(x^(-2)*x^(-5))=(8*x^(-6+5))/(x^(-2+(-5)))=(8*x^(-1))/(x^(-7))=8*x^(-1-(-7))=8*x^(-1+7)=8*x^6`

`8*(-1/2)^6=strike8^1*1/strike64^8=1/8`